Structural recirculation and refractory hypoxemia under femoro‐jugular veno‐venous extracorporeal membrane oxygenation. Issue 8 (8th March 2021) - Charbit, Jonathan; Deras, Pauline; Courvalin, Elie; Laumon, Thomas; Dagod, Geoffrey; Martinez, Orianne; Capdevila, Xavier
Abstract: The performance of each veno‐venous extracorporeal membrane oxygenation (vv‐ECMO) configuration is determined by the anatomic context and cannula position. A mathematical model was built considering bicaval specificities to simulate femoro‐jugular configuration. The main parameters to define were cardiac output (QC ), blood flow in the superior vena cava (QSVC ), extracorporeal pump flow (QEC ), and pulmonary shunt (kS‐PULM ). The obtained variables were extracorporeal flow ratio in the superior vena cava (EFRSVC = QEC /[QEC + QSVC ]), recirculation coefficient (R), effective extracorporeal pump flow (Qeff‐EC = [1 – R] × QEC ), Qeff‐EC /QC ratio, and arterial blood oxygen saturation (SaO2 ). EFRSVC increased logarithmically when QEC increased. High QC or high QSVC /QC decreased EFRSVC (range, 68%‐85% for QEC of 5 L/min). R also increased following a logarithmic shape when QEC increased. The R rise was earlier and higher for low QC and high QSVC /QC (range, 12%‐49% for QEC of 5 L/min). The Qeff‐EC /QC ratio (between 0 and 1) was equal to EFRSVC for moderate and high QEC . The Qeff‐EC /QC ratio presented the same logarithmic profile when QEC increased, reaching a plateau (range, 0.67‐0.91 for QEC /QC = 1; range, 0.75‐0.94 for QEC /QC = 1.5). The Qeff‐EC /QC ratio was linearly associated with SaO 2 for a given pulmonary shunt. SaO2 < 90% was observed when the pulmonary shunt was high (Qeff‐EC /QC ≤ 0.7 with kS‐PULM = 0.7 or Qeff‐EC /QC ≤ 0.8 with kS‐PULM = 0.8). Femoro‐jugular vv‐ECMO generates a systematic structural recirculation that gradually increases with QEC . EFRSVC determines the Qeff‐EC /QC ratio, and thereby oxygen delivery and the superior cava shunt. EFRSVC cannot exceed a limit value, explaining refractory hypoxemia in extreme situations. Abstract : Bicaval model of a vv‐ECMO using the femoro‐jugular configuration.